EXPERIMENTAL STUDY OF LOCAL SOLID WOOD POST-FIRE BEHAVIOUR - Ni Nyoman Kencanawati; B Anshari; J Fajrin; Hariyadi Hariyadi; A Beriman (U Karst, 2020)
When wood structures are exposed to high temperatures, they will decompose to provide a char layer and pyrolysis zone, an insulating material that inhibits further degradation. This experimental study aims to determine the char thickness and pyrolysis of solid wood exposed to fire for 30, 45, and 60 minutes. The post-fire shear strength has also been evaluated. The solid woods were locally from Nusa Tenggara Island, namely Jati Putih, Bajur, and Rajumas. According to the Indonesian National Standard of the heating curve for structures, the temperature growth was SNI-1741: 2008. Obtained The char layer's highest average thickness was within 60 minutes of combustion with the highest temperature of 1055oC. The char layer for Jati Putih, Bajur, and Rajumas are 2.12 mm, 7.89 mm, and 6.53 mm. Meanwhile, the pyrolysis layers are 8.78 mm, 9.13 mm, and 14.82 mm, respectively, for Jati Putih, Bajur, and Rajumas. Besides, the post-fire shear strength of all wood species shows an increase in shear strength in the core. Wood can still sustain the load during a fire because there is a char layer preventing the core section from immediately exposed to the fire.